Soya protein enriched gari - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Most rural areas in developing countries these days are subjected to increasing population densities. The extra food requirement strains still further the already depleted fertility of the soil. As incomes fall demand for cheap staples rises. More...